Moderne Hochgebirgsdarstellung - gezeigt am Beispiel der Alpenvereinskarte Cordillera Real Süd 1:50000 - Finsterwalder, Rüdiger (ERDKUNDE, 1995)
The Alpine Club map Cordillera Real Süd (Illimani) 1: 50 000 includes the most important elements of form found in mountainous regions. In some eases, their cartographic representation has been achieved through the introduction of new techniques. The representation of areas of rock through a linear rock symbol with the retention of equidistant contour lines is a fundamental aspect, as is the representation of debris in grey and the subtly differentiated representation of wooded areas and bushes through a structured green tone. The relief is shown through oblique hatching using uniform grey-blue shading, while a modulated yellow tone is used for areas of vegetation. This map was designed with scientific and touristic purposes in mind, but it could equally well serve as a model for the sheets covering mountainous regions in the official topographic map series 1: 50 000 of the Andean area.